Critical review of design and development of one-stop e-learning plagiarism module for an academic writing course: An application of the ICCEE model - Hussien, Hafizhah Suzana; Khalid, Fariza; Hussin, Supyan; Baharuddin, Dini Farhana; Ab Rahman Z. (Innovare Academics Sciences Pvt. Ltd, 2024)
Indexed by Scopus